(untitled) (Mustansiria Dental Journal, 2018)
Background: This study investigated the influence of light energy density (intensity x time) on the effectiveness of composite cure in view of the curing profiles of lightpolymerization units with different light- activated composites to determine the energy density that satisfies adequate polymerization of all light-activated composites types used in this study. Materials and methods: This study investigated the hardness of the top/bottom surfaces and hardness ratio of 2-mm thick composite specimens after exposure to different light energy densities. Parameters included five light intensities (200, 300, 400, 500 and 600 mW/cm2) and seven curing times (20, 40, 60, 90, 120, 150 and 180 seconds) for each of the four different light-activated composite materials (Tetric Ceram, Heliomolar, Herculite XRV and Degufill Mineral). Results: Statistical analysis of the data by using the one-way analysis of variance revealed that, most of the hardness ratios exhibited a very highly significant difference according to intensity, composite type and curing time. The results indicated that, Heliomolar and Degufill Mineral light-activated composites required approximately (36 J/cm²) energy density for adequate polymerization for a 2-mm thick specimen while, Herculite XRV and Tertric Ceram light-activated composites required approximately (12 J/cm²) energy density for adequate polymerization for a 2-mm thick specimen. Conclusion: This study indicated that, final curing should not be done with energy density less than (300 mW/cm2 for 120 seconds, 400 mW/cm2 for 90 seconds and 600 mW/cm2 for 60 seconds) for Heliomolar and Degufill Mineral light-activated composites.